TLR/MyD88-mediated Innate Immunity in Intestinal Graft-versus-Host Disease - Lee, Young-Kwan (Immune Netw, 2017)
Graft-versus-host disease (GHVD) is a severe complication after allogeneic hematopoietic stem cell transplantation. The degree of inflammation in the gastrointestinal tract, a major GVHD target organ, correlates with the disease severity. Intestinal inflammation is initiated by epithelial damage caused by pre-conditioning irradiation. In combination with damages caused by donor-derived T cells, such damage disrupts the epithelial barrier and exposes innate immune cells to pathogenic and commensal intestinal bacteria, which release ligands for Toll-like receptors (TLRs). Dysbiosis of intestinal microbiota and signaling through the TLR/myeloid differentiation primary response gene 88 (MyD88) pathways contribute to the development of intestinal GVHD. Understanding the changes in the microbial flora and the roles of TLR signaling in intestinal GVHD will facilitate the development of preventative and therapeutic strategies.